2016
DOI: 10.1002/lary.25930
|View full text |Cite
|
Sign up to set email alerts
|

Office‐based biopsies for laryngeal lesions: Analysis of consecutive 581 cases

Abstract: 4. Laryngoscope, 126:2513-2519, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 9 publications
5
28
1
Order By: Relevance
“…As has been observed with other office‐based laryngology procedures, procedure completion rate was high. This was despite several patients either having a diagnosis of generalized anxiety disorder or self‐reporting anxiety related to procedures.…”
Section: Discussionsupporting
confidence: 74%
“…As has been observed with other office‐based laryngology procedures, procedure completion rate was high. This was despite several patients either having a diagnosis of generalized anxiety disorder or self‐reporting anxiety related to procedures.…”
Section: Discussionsupporting
confidence: 74%
“…However, and unlike our study, not all the cases have a confirmatory direct operating room laryngeal biopsy which is the gold standard. [12] The higher diagnostic accuracy and sensitivity of the trans-oral approach in the results of our study is in accordance with the study ofHassan et al (2018) which showed a 100% sensitivity and 75.6% specificity. [13] Healing after office-based superficial laryngeal biopsies generally takes places very quickly and voice rest is not typically required after the procedure [14].…”
Section: Discussionsupporting
confidence: 93%
“…In retrospective analysis, some studies reported somewhat different results as 60% sensitivity and 87% specificity. [8][9][10][11] In a retrospective analysis of consecutive 581 cases, office-based biopsies via trans-nasal approach for laryngeal lesions were evaluated by Cha et al (2016) and the results showed sensitivity of 78.2% and a specificity of 100.0%. However, and unlike our study, not all the cases have a confirmatory direct operating room laryngeal biopsy which is the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…However, and unlike our study, not all of Cha's cases had a confirmatory direct operating room laryngeal biopsy as the gold standard. 12 The higher diagnostic accuracy and sensitivity of the transoral approach in the results of our study agrees with Hassan et al, which showed 100% sensitivity and 75.6% specificity. 13 Healing after office-based superficial laryngeal biopsies generally takes places very quickly, and a voice rest is not typically required after the procedure.…”
Section: Pre-and Postprocedures Precautionssupporting
confidence: 92%